IMPROVEMENT OF HEALTHCARE FACILITY ARCHITECTURE - Sh. A. Egamberdiyeva; J. J. Komilov (Bright Mind Publishing, 2025)
This article provides a scientific analysis of modern approaches, architectural–functional solutions, and innovative technologies aimed at improving the architecture of healthcare facilities. The purpose of the study is to enhance architectural quality by organizing functional zoning in healthcare institutions rationally, optimizing patient flows, ensuring infection safety, increasing energy efficiency, and implementing the principles of a “healing environment.” The research methodology is based on the analysis of regulatory documents, observations in existing medical institutions, interviews with specialists in the field, architectural–functional modeling, and conceptual design processes using BIM technologies.The results of the study show that existing facilities have several issues, such as disproportions in zoning, insufficient performance of air exchange and filtration systems, lack of psychological comfort for patients, and low energy efficiency. The proposed solutions - modular and flexible planning, one-way movement schemes, high-efficiency ventilation systems, biophilic design elements, and the integration of digital BIM technologies - make it possible to significantly improve the functional, sanitary-hygienic, and ecological efficiency of healthcare facilities. The conclusions of the study can be applied in the development of new projects as well as in the reconstruction of existing facilities.
Keywords: Healthcare architecture; functional zoning; patient flow; infection safety; energy efficiency; healing environment; biophilic design; BIM technology; modular planning; medical facilities.